2013
DOI: 10.1007/s00402-013-1742-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute ankle ligament injuries: a systematic review

Abstract: BackgroundLateral ankle sprains are common musculoskeletal injuries.ObjectivesThe objective of this study was to perform a systematic literature review of the last 10 years regarding evidence for the treatment and prevention of lateral ankle sprains.Data sourcePubmed central, Google scholar.Study eligibility criteriaMeta-analysis, prospective randomized trials, English language articles.InterventionsSurgical and non-surgical treatment, immobilization versus functional treatment, different external supports, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
149
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(175 citation statements)
references
References 56 publications
1
149
1
10
Order By: Relevance
“…W gru pie wszyst kich dys cy plin spor to wych czę stość je go wystę po wa nia wy no si od 15 do 20% [1]. Skut ku je ono nie tyl ko uszko dze niem wię za deł, ale rów nież licznych me cha no re cep to rów znaj du ją cych się w ob rę -bie to reb ki sta wo wej, wię za deł czy też ścię gien komplek su sta wu sko ko we go [2][3][4].…”
Section: Wstępunclassified
“…W gru pie wszyst kich dys cy plin spor to wych czę stość je go wystę po wa nia wy no si od 15 do 20% [1]. Skut ku je ono nie tyl ko uszko dze niem wię za deł, ale rów nież licznych me cha no re cep to rów znaj du ją cych się w ob rę -bie to reb ki sta wo wej, wię za deł czy też ścię gien komplek su sta wu sko ko we go [2][3][4].…”
Section: Wstępunclassified
“…Insgesamt herrscht derzeit Konsens über die primäre Durchfüh-rung einer individuellen Therapie, die im Regelfall konservativ durchgeführt werden kann [3,5,6].…”
Section: Therapieunclassified
“…[9][10][11] Because of the relatively high prevalence and risk of ankle sprain, ankle braces are widely used and have been recognized as an effective prophylactic intervention to reduce the incidence, severity, and recurrence of ankle sprains. 4,[12][13][14][15][16][17][18][19][20][21] There are many different types of ankle braces available commercially, and most can be classified into categories of rigid, semi-rigid, or lace-up based upon their general design. A recent study by Denton et al regarding clinicians' (ie, physical therapists and athletic trainers) recommendations and perceptions associated with ankle brace use reported that lace-up braces were the type of ankle brace that were most frequently recommended prophylactically to prevent ankle sprain injuries.…”
Section: Introductionmentioning
confidence: 99%